2021
DOI: 10.2298/sgs2101019j
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of surface characteristics of new rotary nickel-titanium instruments - SEM-EDS analysis

Abstract: Introduction. Modern endodontic procedure implies the use of rotary Ni-Ti instruments during chemomechanical treatment of root canals. The aim of this study is to analyze the surfaces of new (unused) rotary endodontic instruments using the SEM-EDS method and determine how frequently manufacture defects or impurities appear on their working surfaces. Material and method. Five new different sets of rotary endodontic Ni-Ti instruments were included in this study: K3, Mtwo, ProTaper Universal, Hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Medojevic et al demonstrated that clean endodontic instruments represent solely presence of nickel and titanium (in ratio of 55.7:44.3%), while impurities on the files' working surfaces were associated with variety of elements [12]. In present study such elements as C, O and some other minor traces were found even at the areas of working surfaces, which did not present any visual signs of impurities.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Medojevic et al demonstrated that clean endodontic instruments represent solely presence of nickel and titanium (in ratio of 55.7:44.3%), while impurities on the files' working surfaces were associated with variety of elements [12]. In present study such elements as C, O and some other minor traces were found even at the areas of working surfaces, which did not present any visual signs of impurities.…”
Section: Discussionsupporting
confidence: 49%
“…Scanning electron microscopy (SEM) combined with energy dispersive spectrometry (EDS) have been widely used as non-destructive methods in number of *Address correspondence to this author at the National Healthcare University of Ukraine, All-Ukrainian Association of Endodontists, Kyiv, Ukraine; E-mail: bban@i.ua studies provided for the assessment of endodontic files' surface [6,7,9]. Based on the obtained outcomes it was concluded that even new endodontic instruments may demonstrate various surface defects, most of which were related with the specific process of their manufacturing and packaging [6,[11][12][13][14]. On the other hand SEM-EDS approach also helped to revealed that counterfeit endodontic rotary instruments characterized with increased number of different surface defects, while also with prominent SEM-differences compared to original design of the file [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation